2017
DOI: 10.1093/ehjci/jex009
|View full text |Cite
|
Sign up to set email alerts
|

Relation between calcium burden, echocardiographic stent frame eccentricity and paravalvular leakage after corevalve transcatheter aortic valve implantation

Abstract: Calcification of the aortic annulus is associated with a subsequent eccentric shape of the CoreValve prosthesis. This eccentric shape results in more PVL, with the localization of PVL related to the shape of stent frame eccentricity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…Though statistical significance was lost, this trend persisted regardless of BAV performance/omission. Such a finding is unsurprising, given that distortion of the stent as a result of asymmetrical calcium deposition across AV cusps has been highlighted as the most significant contributor to PVL and that significant leaflet asymmetry was observed for both groups in the present study. Other studies, including the large‐scale, observational UK TAVI registry, have also found BAV to be unrelated to the rate of significant residual PVL .…”
Section: Discussionmentioning
confidence: 56%
“…Though statistical significance was lost, this trend persisted regardless of BAV performance/omission. Such a finding is unsurprising, given that distortion of the stent as a result of asymmetrical calcium deposition across AV cusps has been highlighted as the most significant contributor to PVL and that significant leaflet asymmetry was observed for both groups in the present study. Other studies, including the large‐scale, observational UK TAVI registry, have also found BAV to be unrelated to the rate of significant residual PVL .…”
Section: Discussionmentioning
confidence: 56%
“…The association between eccentricity index assessed by MDCT and PVR was first described by Delgado et al [18]. This relation has also been described in vitro [25] and recently, Di Martino et al [26] observed association between calcium score, prosthesis eccentricity and subsequent PVR, however the evaluation of eccentricity was made with TTE, a technique that due to its two-dimensional nature has more limitations to consistently assess geometric morphology. This is the first study to demonstrate independent association between calcium burden, eccentricity evaluated by MDCT and PVR in a cohort of patients undergoing TAVR with either self-expanding and balloon-expandable prosthesis.…”
Section: Geometry and Paravalvular Regurgitationmentioning
confidence: 84%
“…As the quantity and asymmetry of aortic valve calcification predict the severity of post-procedural PVL, [39][40][41][42][43][44] compared with direct TAVI with balloon-expandable valves. 18,27 Of note, valve repositioning during implantation of newer self-expanding devices could arguably represent a form of mild predilatation; however, the relative role of this step with respect to pre-BAV is currently unknown.…”
Section: Paravalvular Leakagementioning
confidence: 99%